Development and Pretesting of Risk-Based Mobile Multimedia Message Content for Young Adult Hookah Use. (December 2019) - Johnson, Andrea C.; Lipkus, Isaac; Tercyak, Kenneth P.; Luta, George; Rehberg, Kathryn; Phan, Lilianna; Abroms, Lorien C.; Mays, Darren
Background . Hookah is one of the most commonly used tobacco products among U.S. young adults due in part to widespread misperceptions that it is not harmful or addictive. There is growing evidence that hookah tobacco is associated with health harms and can lead to addiction. Research on interventions to address these misperceptions by communicating the harms and addictiveness of hookah use is needed. Aims . This study developed and pretested mobile multimedia message service (MMS) message content communicating the risks of hookah tobacco use to young adult hookah smokers. Method . Message content, delivery, and pretesting were tailored to participants' risk beliefs, hookah use frequency, and responses to simulated text message prompts. Participants viewed 4 of 12 core MMS messages randomized within-subjects and completed postexposure measures of message receptivity and emotional response (e.g., worry). Results . The sample included 156 young adult (age 18-30 years) hookah smokers; 31% smoked hookah monthly and 69% weekly/daily. Prior to viewing messages, a majority endorsed beliefs reflecting misperceptions about the risks of hookah tobacco. Postexposure measures showed participants were receptive to the messages and the messages evoked emotional response. As anticipated, messages produced similar receptivity and there were few differences in emotional response between the messages tested. Discussion . Young adult hookah tobacco smokers were receptive to tailored mobile MMS messages and messages evoked emotional response, two critical precursors to behavior change. Conclusion . Findings indicate that research testing the efficacy of tailored MMS messaging as a strategy for reducing hookah tobacco use in young adults is warranted.